Virtual Self in Dysfunctional Internet Use - Rowiński, Tomasz (Studia Psychologica: Theoria et praxis, 2008)
In contemporary psychology information and communication technology (ICT) have become the object of study. Especially, the relationship between self and virtual space was explored (Hermans, 2004; Hevern, 2004; Ligorio & Spadaro, 2005; Talamo & Ligorio, 2001; Turkle, 1995). Various interactions between self and Internet activity were discovered, in which virtual identity plays an important role. On the one hand these interactions are a chance to discover and develop the self through online experience, but on the other hand they might be destructive for individual life (Davis, 2001; Young, 1998). Dialogical Self Theory may propose some new ideas and interpretations which will allow to understand better the influence of Internet on human beings. The sample used in the research presented here includes 339 participants – high school pupils, college students and employees. The Canonical Correlation Analysis and Discriminant Analysis were applied to estimate predictors of pathological Internet use operationalizated in Rowinski’s (2006) questionnaire. The results show that emotional aspect of online and offline behavior are the strongest predictors of dysfunctional Internet use. The feelings connected with motive S and O with intensive positive feelings in valuation of Internet and with negative feelings in valuation of close relationship have the strongest impact on dysfunctional Internet use. Positions that depend on the Internet use are probably the most dominant in a multivoice system of the self. At the same time positions related to offline reality are marginalized. The dialogical nature of the self might be limited to intensive interaction based on online activity. To check this hypothesis, however, further research is needed.